Primary and acquired resistance to biologic therapies in gastrointestinal cancers - Lubner, Sam J.; Uboha, Nataliya V.; Deming, Dustin A. (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
Improvements in the understanding of cancer biology have led to therapeutic advances in the treatment of gastrointestinal cancers. Drugs which target the vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) pathways have led the way in colon cancer. Monoclonal antibodies (mAbs) such as bevacizumab, ramucirumab, cetuximab, and panitumumab, have improved progression free survival and overall survival (OS) for colorectal cancers and were quickly adopted. Human epidermal growth factor receptor 2 (HER2) has demonstrated significant benefit for gastroesophageal cancers and in the setting of HER2 amplification, trastuzumab in combination with chemotherapy has become the standard of care. However, responses have not been as durable nor as robust as once hoped. Mechanisms of resistance for each of these biologic compounds have been hypothesized and are in the process of being better elucidated. This review will approach the innate and acquired mechanisms of resistance of the above compounds. Additionally, we will explore some ongoing clinical trials to capitalize on the mechanisms of resistance in the hopes of retaining the promise of targeting these pathways.